Formation of an interstitially alloyed phase in Mg/C60 composite - Shin, Jaehyuck; Yoon, Sock-yeon; Choi, Hyunjoo; Shin, Seeun; Bae, Donghyun (Metals and materials international, 2013)
The formation of an interstitially alloyed phase and its effects on mechanical properties are investigated for a magnesium-based composite containing fullerene (Mg/C 60 ). The Mg/C 60 composite was fabricated using the ball milling method followed by hot rolling and then the composite sheet was annealed at 425°C for up to 37 h. The fullerene was dispersed during the ball milling process and it was decomposed. The carbon atoms from the decomposed fullerene diffused into the magnesium matrix, which increasingly occupied the octahedral sites of the magnesium as the annealing continued. The formed interstitially alloyed phase expanded as the annealing time increased, and magnesium carbide was formed after 37 h. Vickers hardness value increased as the interstitially alloyed phase continuously formed and it decreased when the magnesium carbide was formed, because the carbon atoms at the magnesium interstices may interact with moving dislocations, resulting in an increase in the hardness of the magnesium.